1970
DOI: 10.4315/0022-2747-33.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Types and Populations of Microorganisms in the Air of Fluid Milk Plants

Abstract: Airborne viable particle counts in the milk processing areas of 10 dairy plants averaged 14 molds and 32 non-molds/10 liters. The bacteria isolated were primarily micrococci, Gram-negative rods (excluding coliform), bacilli, and coryne-bacteria. Twenty-five per cent of the isolates grew at 10 C in 5 days. These were principally bacilli and Gram-negative rods (excluding coliform). There was no apparent relationship between airborne microbial populations and keeping quality of the packaged milk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1973
1973
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The experimental conditions aimed to investigate the effect at the beginning of the production operation, since the occurrence of an adverse effect present at this stage should continue to act. The results suggest that further studies should consider investigating the possibility of post contamination, as suggested by Cannon (1970).…”
Section: Resultsmentioning
confidence: 85%
“…The experimental conditions aimed to investigate the effect at the beginning of the production operation, since the occurrence of an adverse effect present at this stage should continue to act. The results suggest that further studies should consider investigating the possibility of post contamination, as suggested by Cannon (1970).…”
Section: Resultsmentioning
confidence: 85%
“…1958; Heldman et al . 1964; Cannon 1966; Heldman et al . 1966) indicated that bacteria, yeasts and moulds are continuously falling from the air in a dairy factory.…”
Section: Resultsmentioning
confidence: 99%
“…1966) indicated that bacteria, yeasts and moulds are continuously falling from the air in a dairy factory. Cottage cheese is exposed to airborne contamination when open vats are used and during filling (Cannon 1966). Ripened cheeses are exposed when cheese is made in open vats and during packaging.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aerial contamination in milk processing plants has been assessed by Labots (1961) and Cannon (1970), the former recording that in some cases the bacterial isolates were mainly Gram-negative. In farm cowsheds and milking parlours 161 l62 J. T. PATTERSON Benham and Egdell (1970) identified their isolates mainly as Gram-positive cocci, Gram-positive non-sporing rods and Bacillus spp.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%